2019
DOI: 10.3390/ijms20163928
|View full text |Cite
|
Sign up to set email alerts
|

Zr-89 Immuno-PET Targeting Ectopic ATP Synthase Enables In-Vivo Imaging of Tumor Angiogenesis

Abstract: In this study, we synthesized a Zr-89-labeled anti-adenosine triphosphate synthase monoclonal antibody (ATPS mAb) for applications in immuno-positron emission tomography (PET) and evaluated its feasibility for angiogenesis imaging. The cellular uptake of Zr-89 ATPS mAb was measured after treatment of cancer cell lines in vitro, and its biodistribution was evaluated at 4, 24 and 48 h in vivo in mice bearing xenografts. PET images were acquired at 4, 24, 48, and 96 h after Zr-89 ATPS mAb administration. Tumor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…The whole antibody was a superior tracer probably due to larger size (preventing renal clearance), longer systemic retention, and better protein stability in vivo as compared to the smaller formats. Our results agree with similar studies where smaller formats were not necessarily better in tumor targeting and accumulation than full antibodies. We think that the the enzymatically generated Fab′2 fragment suffers from reduced stability in vitro and in vivo, which could be improved using mammalian expression and therefore needs further investigation. High renal uptake and retention of 89 Zr-conjugated Fc-less short antibody formats could be avoided by using renal radio-protectants.…”
Section: Resultssupporting
confidence: 89%
“…The whole antibody was a superior tracer probably due to larger size (preventing renal clearance), longer systemic retention, and better protein stability in vivo as compared to the smaller formats. Our results agree with similar studies where smaller formats were not necessarily better in tumor targeting and accumulation than full antibodies. We think that the the enzymatically generated Fab′2 fragment suffers from reduced stability in vitro and in vivo, which could be improved using mammalian expression and therefore needs further investigation. High renal uptake and retention of 89 Zr-conjugated Fc-less short antibody formats could be avoided by using renal radio-protectants.…”
Section: Resultssupporting
confidence: 89%
“…Therefore, ATPS could serve as a novel target for anti-angiogenic cancer therapies. As previously demonstrated, the anti-ATPS mAb used in this study can target tumor vasculature and cancer cells [ 9 ]. In this study, 177 Lu-DOTA-ATPS mAb showed a significant inhibitory effect on MKN-45 gastric cancers.…”
Section: Discussionmentioning
confidence: 86%
“…Radioiodine ( 131 I)-labeled anti-ATPS antibody effectively suppressed the tumor growth by 2.5-fold in a gastric cancer model [ 8 ]. Anti-ATPS antibodies labeled with Zirconium-89 ( 89 Zr) demonstrated significantly higher targeting specificity for MDA-MB-231 tumors with abundant ectopic ATPS expression compared to PC-3 tumors with low expression [ 9 ]. Given its role in tumor angiogenesis, ectopic ATPS emerges as a novel target for developing effective anti-angiogenic therapies.…”
Section: Introductionmentioning
confidence: 99%
“… 37 , 38 Moreover, MAS is able to modulate the astrocyte inflammatory response, which is related to the initiation of glioma. 39 , 40 …”
Section: Atp Synthase Is Required For Malignant Tumor Growthmentioning
confidence: 99%